Switched-flux machines with hybrid NdFeB and ferrite magnets. Issue 2 (7th March 2016) - Afinowi, I.A.A.; Zhu, Z.Q.; Guan, Y.; Mipo, Jean-Claude; Farah, P.
Abstract : Purpose: – The purpose of this paper is to comparatively study the conventional, i.e. single magnet, and novel hybrid-magnet switched-flux permanent-magnet (HMSFPM) machines. Design/methodology/approach: – The HMSFPM machines utilize two magnet types, i.e. low-cost ferrites and NdFeB. Thus, a set of magnet ratios (?), defined as the quotient of the NdFeB volume to the total PM volume, is introduced. This allows any desired performance and cost trade-off to be designed. Series- and parallel-excited magnet configurations are investigated using 2-dimensional finite element analysis. Findings: – The torque of the HMSFPM machines is lower than the NdFeB SFPM machine but the flux-weakening performance is improved for similar machine efficiency. If the machine dimensions are unconstrained, the HMSFPM machines can have the same torque for reduced material costs and a moderate increase in machine dimensions. Ferrite SFPM machines have the lowest cost for the same torque but a significant increase in machine dimensions is required. Finally, the series-excited HMSFPM machine is the preferred over the parallel-excited HMSFPM machine because it has superior demagnetization withstand capability. Research limitations/implications: – Mechanical and winding eddy current losses are not considered in the efficiency map calculations. Originality/value: – The NdFeB SFPM, ferrite SFPM, series-excited HMSFPM, and the parallel-excited HMSFPM machines are compared for their electromagnetic performance, flux-weakening, PM demagnetization, efficiency, and material costs.